FunResDB—A web resource for genotypic susceptibility testing of Aspergillus fumigatus. (11th March 2017) - Weber, Michael; Schaer, Jonas; Walther, Grit; Kaerger, Kerstin; Steinmann, Jörg; Rath, Peter-Michael; Spiess, Birgit; Buchheidt, Dieter; Hamprecht, Axel; Kurzai, Oliver
Abstract: Therapy of invasive aspergillosis is becoming more difficult due to the emergence of azole resistance in Aspergillus fumigatus . A majority of resistant strains carries mutations in the CYP51A gene. Due to a lack of sensitivity of culture-based methods, molecular detection of A. fumigatus has become an important diagnostic tool. We set up the database FunResDB (www.nrz-myk.de/funresdb ) to gather all available information about CYP51A -dependent azole resistance from published literature. In summary, the screening resulted in 79 CYP51A variants, which are linked to 59 nonsynonymous mutations. A tailor-made online sequence analysis tool allows for genotypic susceptibility testing of A. fumigatus .